Physiological and Pharmacological Roles of FGF21 in Cardiovascular Diseases - Peng Cheng; Fangfang Zhang; Lechu Yu; Xiufei Lin; Luqing He; Xiaokun Li; Xuemian Lu; Xiaoqing Yan; Yi Tan; Chi Zhang (Journal of Diabetes Research, 2016)
Cardiovascular disease (CVD) is one of the most severe diseases in clinics. Fibroblast growth factor 21 (FGF21) is regarded as an important metabolic regulator playing a therapeutic role in diabetes and its complications. The heart is a key target as well as a source of FGF21 which is involved in heart development and also induces beneficial effects in CVDs. Our review is to clarify the roles of FGF21 in CVDs. Strong evidence showed that the development of CVDs including atherosclerosis, coronary heart disease, myocardial ischemia, cardiac hypertrophy, and diabetic cardiomyopathy is associated with serum FGF21 levels increase which was regarded as a compensatory response to induced cardiac protection. Furthermore, administration of FGF21 suppressed the above CVDs. Mechanistic studies revealed that FGF21 induced cardiac protection likely by preventing cardiac lipotoxicity and the associated oxidative stress, inflammation, and apoptosis. Normally, FGF21 induced therapeutic effects against CVDs via activation of the above kinases-mediated pathways by directly binding to the FGF receptors of the heart in the presence of β-klotho. However, recently, growing evidence showed that FGF21 induced beneficial effects on peripheral organs through an indirect way mediated by adiponectin. Therefore whether adiponectin is also involved in FGF21-induced cardiac protection still needs further investigation.